Composite indexing for nutritional status evaluation: A snapshot of malnutrition across India - Neeraj Agarwal; Neha Chaudhary; Pankaj Kumar Pathak; Avneet Randhawa (Wolters Kluwer Medknow Publications, 2020)
Introduction: Data from several sources revealed that huge incongruity persists in nutritional status across the states in India. Thus, this study was undertaken to generate a nutritional index, so that these disparities could be quantified and comparison be done. Materials and Methods: A nutritional index for 21 major states of India has been constructed on the basis of eight important nutrition-related indicators. The scaled value of each indicator for all the states was calculated. Each indicator was assigned an arbitrary weight (Wi) on the basis of its impact on nutritional status. On the basis of the scaled value and weight given to the particular indicator, a composite-weighted index was thus calculated. Results: States were ranked on their nutritional status as per the final composite score they attained. Out of 21 major states, Kerala took the top position followed by Jammu and Kashmir and Himachal Pradesh on the 2nd and 3rd position, respectively, while Uttar Pradesh got the lowest rank followed by Bihar and Jharkhand on the 2nd and 3rd lowest positions. Conclusion: Our study concludes that not taking an account of the burden of malnutrition when disbursing funds leads to ineffective implementation of various nutritional programs. Integrated Child Development Services has already been brought in mission mode under Poshan Abhiyan. Other determinants, i.e., illiteracy, poor sanitation, diseases, and infections, should also be considered and addressed through nutritional programs.